Temporary Sequestration Credits : An Instrument for Carbon Bears - Kenneth M. Chomitz; Franck Lecocq (World Bank, Washington, DC, 2014)
Temporary crediting of carbon storage is a proposed instrument that allows entities with emissions reductions obligations to defer some obligations for a fixed period of time. This instrument provides a means of guaranteeing the environmental integrity of a carbon sequestration project. But because the user of the temporary credit takes on the liability of renewing it, or replacing it with a permanent credit, the temporary credit must sell at a discount compared with a permanent credit. The authors show that this discount depends on the expected change in price of a permanent credit. Temporary credits have value only if restrictions on carbon emissions are not expected to tighten substantially. The intuition is illustrated by assessing the value of a hypothetical temporary sulfur dioxide sequestration credit using historical data on actual sulfur dioxide allowance prices.